The Effectiveness of the Curriculum for Indonesian Education Quality Standards According to Rusdi Ahmad Thu'aimah - Jasuli, Jasuli; Achmad Muhlis (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
The curriculum is a central component of the educational system because it serves as the foundation for formulating learning objectives, materials, methods, and assessments. In Indonesia, the curriculum is designed to respond to the National Education Standards (SNP), which encompass eight aspects ranging from content standards to assessment. One prominent figure relevant to curriculum development, particularly in the field of language education, is Rusydi Ahmad Thu’aimah. He emphasizes that the selection and organization of learning materials must be based on linguistic, educational, psychological, and social principles, and should be arranged gradually, proportionally, and contextually. This paper discusses the relevance of Thu’aimah’s theories to the Indonesian curriculum, analyzes the effectiveness of its implementation using the indicators he proposed, and provides recommendations for improvement. The findings indicate that although Indonesia’s curriculum has incorporated competency-based and differentiated learning, challenges remain in the quality of teaching materials, the role of teachers as facilitators, and an evaluation system that overemphasizes cognitive aspects. Therefore, improvements are needed through the formulation of operational objectives, the enhancement of teaching materials and textbooks, the application of active learning methods, and more holistic evaluation practices. With these improvements, the Indonesian curriculum is expected to better align with educational quality standards while also adhering to the principles of effective material development as proposed by Rusydi Ahmad Thu’aimah.